Male Victims at a Dutch Sexual Assault Center: A Comparison to Female Victims inCharacteristics and Service Use - Covers, Milou L. V. (Journal of interpersonal violence, 2022)
Recently, there has been an increase in referrals of male victims of sexual assault to interdisciplinary sexual assault centers (SACs). Still, there is limited research on the characteristics of men who refer or are referred to SACs and the services they need. To facilitate the medical, forensic, and psychological treatment in SACs, a better understanding of male victims is indispensable.The first aim of the study was to analyze the victim and assault characteristics of male victims at a Dutch SAC, and to compare them to those of female victims. The second aim was to analyze and compare SAC service use between male and female victims.The victim characteristics, assault characteristics, and service use of 34 male victims and 633 female victims were collected in a Dutch SAC. T-tests and chi-square tests were used to analyze differences between male and female victims.No differences between males and females in victim or assault characteristics were found. Most victims received medical and psychological care, with no differences between male and female victims. Female victims were more likely to have contact with the police, but no differences in reporting or forensic medical examinations between males and females were found.These findings indicate that SACs can and do provide equal services to male and female victims, and that the current services are suitable for male victims as well. However, a focus on educating and advising male victims about police involvement is advisable.